2000
DOI: 10.1117/12.401619
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PSTM with A-SNOM

Abstract: A comparison between PSTM and A-SNOM in resolution, contrast and optical efficiency is discussed. The order of magnitude roughly estimated shows that PSTM is much better than commercial A-SNOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Based on these three invented patents, the first resolution NOM of AF / PSTM (combination of vertical resonance mode AFM with PSTM ) was developed and passed the appraisal organized by the experts group of National Ministry of Education in 2002 [32,33]. The results of functional examination experiments have shown that AF/PSTM prototype is much better than A-SNOM [34]. There are three advantages of this system [35]: (1) It can eliminate the optical false image in PSTM; (2) The optical image and topographic image of sample are separated with AF / PSTM; (3) During scanning two optical images (refractive index image and transmissivity image) and two AFM images (topography and phase) can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these three invented patents, the first resolution NOM of AF / PSTM (combination of vertical resonance mode AFM with PSTM ) was developed and passed the appraisal organized by the experts group of National Ministry of Education in 2002 [32,33]. The results of functional examination experiments have shown that AF/PSTM prototype is much better than A-SNOM [34]. There are three advantages of this system [35]: (1) It can eliminate the optical false image in PSTM; (2) The optical image and topographic image of sample are separated with AF / PSTM; (3) During scanning two optical images (refractive index image and transmissivity image) and two AFM images (topography and phase) can be obtained.…”
Section: Introductionmentioning
confidence: 99%